Comparison of digital research skills between Spain and Ecuador - Juan José Victoria-Maldonado; Yosbanys Roque-Herrera; Blanca Berral-Ortiz; Alejandra Salomé Sarmiento-Benavides (Je-LKS: Journal of E-Learning and Knowledge Society)
The idea of the university as a mere transmitter of knowledge has long been obsolete. In the context of educational research and innovation, it is university teachers who fulfill these roles. This shift, along with the technological advancements of the 21st century, highlights the need for a thorough investigation into how well university teachers are equipped to face these new challenges. Consequently, various tools have been developed to provide a research framework that allows for comparisons between countries. Tools such as DigCompEdu have been used to assess teachers' digital competencies and to facilitate cross-country comparisons. However, this study does not focus on teaching competencies but rather on exploring research competencies related to ICTs. In this context, a comparison is made between Spain and Ecuador to examine how two institutions from different countries operate, as well as how they function in relation to gender and the stage of academic career development. This aims to identify aspects that can serve as distinguishing factors. The results show that there are no significant differences in the comparison of researchers from the two universities, finding significant changes only for specific aspects, establishing as differentiating factors the idea of a greater intention to use ICT for research by researchers at the University of Granada and showing how during the training of university teachers, confidence is acquired to train new researchers, establishing the ideal time for training once they have more than 10 years of research and with a permanent university link.